2009
DOI: 10.1039/b810230a
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and reduced Roussin's red salt ester [Fe2(μ-RS)2(NO)4] (R = n-Pr, t-Bu, 6-methyl-2-pyridyl and 4,6-dimethyl-2-pyrimidyl): synthesis, X-ray crystal structures, spectroscopic, electrochemical and density functional theoretical investigations

Abstract: A series of Roussin's red salt esters [Fe 2 (μ-RS) 2 (NO) 4 ] (R = n-Pr (1), t-Bu (2), 6-methyl-2-pyridyl (3) and 4,6-dimethyl-2-pyrimidyl (4)) were synthesized by the reaction of Fe(NO) 2 (CO) 2 with thiols or thiolates. Complexes 1-4 were characterized by IR, UV-vis, 1 H-NMR, electrochemistry, and single-crystal X-ray diffraction analysis. The IR spectra of complexes 1-4 display one weak and two strong NO stretching frequencies (ν NO ) in solution, but only two strong ν NO in the solid. Density functional th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 87 publications
6
54
0
Order By: Relevance
“…It has been demonstrated that the carbonyl groups of Fe(NO) 2 (CO) 2 can be easily replaced by phosphorus-containing or sulfur-containing ligands to produce the dinitrosyl complexes as reported in previous studies 13,18. In rare cases, it can be replaced by nitrogen-contained ligands 9,10.…”
Section: Resultsmentioning
confidence: 55%
“…It has been demonstrated that the carbonyl groups of Fe(NO) 2 (CO) 2 can be easily replaced by phosphorus-containing or sulfur-containing ligands to produce the dinitrosyl complexes as reported in previous studies 13,18. In rare cases, it can be replaced by nitrogen-contained ligands 9,10.…”
Section: Resultsmentioning
confidence: 55%
“…The characteristic nitrosyl stretching frequencies (ν NO, CH 2 Cl 2 1789 and 1732 cm −1 ) of complex 1 is similar to the reported values (ν NO, (THF) 1789 and 1736 cm −1 ) of DNICs with bidentate [N,S] ligands [7e]. When comparing with the dinuclear iron complexes [Fe 2 (μ-RS) 2 (NO) 4 ] (R = n-Pr, tBu, 6-methyl-2-pyridyl and 4,6-dimethyl-2-pyrimidyl) with [S,S] ligation [13] and cyclic tetra-nuclear iron complex [Fe(NO) 2 (Im-H)] 4 (Im = imidazole) with [N,N] ligation [7c] (Scheme 1), their IR spectra bear the same pattern but differ in the position (ν NO, (CH 2 Cl 2 ) 1789 and 1732 cm −1 for 1 vs 1797-1775 and 1763-1748 cm −1 for [Fe 2 (μ-RS) 2 (NO) 4 ] and 1801 and 1735 cm −1 for [Fe(NO) 2 (Im-H)] 4 ) and the separation of NO stretching frequencies Δν NO (~57 cm −1 for 1 vs ~29 cm −1 for [Fe 2 (μ-RS) 2 (NO) 4 ] and ~66 cm −1 for [Fe(NO) 2 (Im-H)] 4 . These results suggest that the position and Δν NO of IR spectrum may serve as an efficient tool for the discrimination of the existence of the neutral dinuclear iron nitrosyl complexes containing the variety of [N,N]/[N,S]/[S,S] ligations.…”
Section: Resultsmentioning
confidence: 87%
“…Two benzimidazolyl planes are almost parallel to each other along opposite direction and form an angle of ~113°with the 2Fe-2S plane. The Fe(1)-Fe(1a) distance of ca 4.14 Å shows that there is almost no interaction between the two iron centers, which is clearly differed from dinuclear iron complexes [Fe 2 (μ-RS) 2 (NO) 4 ] (ca 2.70 Å) [13]. The Fe-S and Fe-N(imidazole) bond distance for complex 1 is 2.3032(7) and 2.0222(16) Å, respectively, which is longer than the relevant Fe-S distance (ca 2.267 Å) in the [Fe 2 (μ-RS) 2 (NO) 4 ] [13] and Fe-N(imidazole) (ca 2.009 Å) in the [Fe(NO) 2 (Im-H)] 4 [7c].…”
Section: Resultsmentioning
confidence: 99%
“…Different synthetic ways are described for the dinuclear RRSE preparations: nitrosylation of Fe(II) and thiolate mixed solution with NO g [13]; S-alkylation of Roussin's red salt Na 2 [Fe 2 (l-S) 2 (NO) 4 4 ] are available with aliphatic [3,17], aromatic [18,19], peptide bound [20], and inorganic [21,22] substituents. Different ''aliphatic'' DNICs with primary [23,24] and tertiary [25,26] thiolate ligands are known, yet binuclear DNICs with secondary thiols (R 2 CH-SH) were not earlier structurally characterized by X-ray diffraction analysis. The n-propyl DNIC [Fe 2 (l-Sn Pr) 2 (NO) 4 ] was synthesized and its structure was determined by XRD crystallography to be centrosymmetric by Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The n-propyl DNIC [Fe 2 (l-Sn Pr) 2 (NO) 4 ] was synthesized and its structure was determined by XRD crystallography to be centrosymmetric by Ref. [23]. A complex with benzyl substituent at the sulfur bridging atom was described by Lippard and co-workers [19] and with the ethyl substituent, by Lu et al [27].…”
Section: Introductionmentioning
confidence: 99%